Ilmu Kefarmasian Dalam Prespektif Islam dan Kemuhammadiyaan - Ria Indah Pratami; Oman Fathurohman sw (STIKes Ibnu Sina Ajibarang, 2024)
The pharmaceutical world today has developed very quickly, and this development has seen a shift in focus to current products. The principles of treatment that contain high and noble values ​​emerged from the revelation of the Koran and Islamic teachings conveyed by the Prophet Muhammad. This research aims to analyze pharmaceutical science from an Islamic and Muhammadiyah perspective, with a focus on developing a pharmaceutical practice model that is based on the ethical and moral values ​​taught by Islam. The method used is literature research with data sources from published research. Literature review involves reading books, journals, and other publications related to the research topic in order to write about the subject. Based on research findings, pharmaceutical practitioners and health institutions apply Islamic and Muhammadiyah principles in their practice, thereby making a significant contribution to improving the quality of health services and welfare of the people through an ethical, moral and sustainable approach in accordance with Islamic teachings and Muhammadiyah values